HAK EKONOMI DAN SOSIAL PADA LANSIA DI INDONESIA - Rochma Putri, Ika Nanda; Afifah, Wiwik (Journal Evidence Of Law, 2022)
The increasing number of years of population growth in Indonesia is also accompanied by an increase in the number of elderly people or commonly referred to as elderly. Some of the factors that make the elderly population limited are mobility which makes it difficult for the elderly to be productive, unable to meet their needs and need help from others. The elderly cannot be separated from 3 things, namely poverty, neglect and protection. These three things are the main problems that every elderly will find the role of the community such as the existence of social assistance institutions and the formation of legislation and various social welfare programs that have begun to be seen being implemented in the community. However, the implementation is not always right on target, one of which is often found in the problem of social assistance, there are still many in some areas in Indonesia, especially remote areas where the elderly population lives alone without any family paying attention so that their social economic needs are limited. Therefore, the fulfillment of social economic rights for the elderly is very necessary considering that the elderly are a vulnerable group whose human rights must be protected.